The Relationship of Mother's Knowledge with the Selection of Educational Game Tools among Preschool Age Children during the COVID-19 Pandemic - Hindyah Ike Suhariati; Ifa Nofalia (Babali Nursing Research, 2022)
Introduction: Most parents or mothers do not understand about educational game tools, even many of them buy beautiful and interesting game tools but they do not think what to do with these game tools. In this case, if children are left in this condition, in the end this can actually be counterproductive to the purpose of education itself and interfere the growth process of preschool age children (4-6 years). The purpose of this study is to know the relationship of mother’s knowledge with the selection of educational game tools among preschool age children during the COVID-19 pandemic. Methods: The design of this study used cross-sectional analysis with a population of all mothers who have preschool children at Al Husna Tembelang Islamic Kindergarten, Jombang with a sample of 40 people using simple random sampling technique. The data was collected through a questionnaire, then to determine the relationship between the two variables, the Spearman Rank statistical test was carried out with a significance level of = 0.05. Results: The results showed that most of the mothers had good knowledge of 52.6% while the selection of educational game tools was 50% according to the age of the children. Based on the results of the Spearman Rank correlation test, the value of < or 0.000 < 0.05. Conclusion: The conclusion of this study there is a relationship between mother's knowledge and the selection of educational game tools for preschool age children during the COVID-19 pandemic at Al Husna Tembelang Islamic Kindergarten, Jombang.